2012
DOI: 10.1038/eye.2012.253
|View full text |Cite
|
Sign up to set email alerts
|

Inflammation in uveal melanoma

Abstract: Leukocytic infiltration is a common feature of human cancers, including those that develop in immunoprivileged sites, such as the eye. The infiltration of myeloid and T cells into tumours is part of the host response against cancer. In uveal melanoma, high densities of immune cells seem to be involved in tumour progression, as they are associated with the loss of one chromosome 3. The nature of this tumour microenvironment might offer therapeutic opportunities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
67
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(69 citation statements)
references
References 47 publications
1
67
0
Order By: Relevance
“…We observed that HDAC4 expression was strongest for the cytoplasmic area and intensity in uveal melanoma. HDAC4 is often upregulated in malignancies with excess inflammation and chemokine signalling [30], consistent with an inflammatory phenotype known to enhance the progression of uveal melanoma [31]. In some immune cells, controlled nuclear export of HDAC4 plays an important role in cytokine production [28].…”
Section: Discussionmentioning
confidence: 99%
“…We observed that HDAC4 expression was strongest for the cytoplasmic area and intensity in uveal melanoma. HDAC4 is often upregulated in malignancies with excess inflammation and chemokine signalling [30], consistent with an inflammatory phenotype known to enhance the progression of uveal melanoma [31]. In some immune cells, controlled nuclear export of HDAC4 plays an important role in cytokine production [28].…”
Section: Discussionmentioning
confidence: 99%
“…These include a large tumor diameter and prominence, localization in the ciliary body, a high mitotic count, and the presence of epithelioid cells and a leukocytic infiltrate. [6][7][8][9] Specific genetic features are also correlated with prognosis: the importance of chromosome 3 loss and chromosome 8q gain was identified first, [10][11][12] and subsequent studies showed that aberrations such as loss of chromosomes 1p, 6q, and 8p and gain of chromosome 6p have prognostic value as well. [13][14][15] Although loss of one copy of chromosome 3 is the aberration most strongly associated with poor prognosis, a combination with gain of chromosome 8q is more strongly correlated with metastatic UM than either of the two aberrations alone.…”
Section: Methodsmentioning
confidence: 99%
“…Immune responses against melanoma antigens may play a role in either preventing the growth of the primary tumor or the development of metastases. Indeed, several studies have indicated that an increased expression of HLA molecules confers an increased risk to develop metastases [48,59]. However an association between either the development of UM or its metastases and HLA type was not observed: a recent Dutch large-scale study examined which HLA alleles were related to the development of UM or associated with any specific clinical or tumor characteristics.…”
Section: Somatic Events and Mutationmentioning
confidence: 94%
“…Metastatic death occurs almost exclusively in patients with chromosome 3 loss and/or a specific mRNA gene expression profile, known as class 2 [58]. As has been reported for CM and cancer in general, other parameters related to poor prognosis might include immunological determinants [59]. Immune responses against melanoma antigens may play a role in either preventing the growth of the primary tumor or the development of metastases.…”
Section: Somatic Events and Mutationmentioning
confidence: 97%